STATUS BEKERJA, STRUKTUR KELUARGA DAN KERAWANAN PANGAN RUMAH TANGGA DENGAN ANAK - Hepi Yunita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2021)
AbstractHousehold food insecurity is an important issue because of its negative impact on children’s health and nutrition. This study aimed to analyze the effect of working status and family structure on food insecurity in households with children. The data used comes from the 2018 National Socio-Economic Survey. The analysis was carried out separately for poor and non-poor households using binary logistic regression. The results showed that households with heads in part-time work and those with unemployed heads were more likely to be food insecure than households with heads in full-time work in both households, whereas households with heads not in labor force were significantly more likely to be food insecure only in the poor households. In the poor households, single-male headed households were more likely to be food insecure than single-female headed households while in the non-poor households, the opposite occurred. Strengthening social safety nets, expanding employment opportunities and providing education about food insecurity needs to be done in households with children.